2018
DOI: 10.1037/ort0000240
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and post-migration psychological symptoms among Iraqi refugees: A path analysis.

Abstract: Refugees frequently experience symptoms of posttraumatic stress and depression, which impede their acculturation in the new host country where they are resettling. There are few longitudinal studies investigating predictors of mental health and acculturation during the early postmigration period. We conducted a longitudinal study of 298 Iraqi refugees, assessing them upon arrival to the U.S. and 1 year after migration. Premigration trauma was associated with increased PTSD and depressive symptoms at baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 57 publications
0
53
0
4
Order By: Relevance
“…These two factors could interact to increase pain and depression, as social support represents an important buffer against stress 35, 46 ; hence, the combination of acculturation stress and low social support may be particularly potent. In addition, the impact of acculturation stress and low social support may be magnified among Asian Americans with comorbid pain and depression; both are risk factors for pain and depression, 34, 37, 45, 59 which can, in turn, be mutually exacerbating. Moreover, cultural traditions that emphasize stoicism (e.g., Confucianism) may prevent Asian Americans from seeking adequate treatment for pain and depression; consequently, the severity of their pain and depressive symptoms may increase.…”
Section: Discussionmentioning
confidence: 99%
“…These two factors could interact to increase pain and depression, as social support represents an important buffer against stress 35, 46 ; hence, the combination of acculturation stress and low social support may be particularly potent. In addition, the impact of acculturation stress and low social support may be magnified among Asian Americans with comorbid pain and depression; both are risk factors for pain and depression, 34, 37, 45, 59 which can, in turn, be mutually exacerbating. Moreover, cultural traditions that emphasize stoicism (e.g., Confucianism) may prevent Asian Americans from seeking adequate treatment for pain and depression; consequently, the severity of their pain and depressive symptoms may increase.…”
Section: Discussionmentioning
confidence: 99%
“…Other recent research on Iraqi refugees had also found elevated psychological distress (Hengst et al, 2018;Al-Smadi et al, 2017) but did not report potential differences by ethnic identification or religious affiliation. However, an earlier cohort of Iraqi refugees (10% Muslims) in southeast Michigan recruited after the Iraq War of 2003-2011 ended but prior to the arrival of ISIS found low levels of distress (LeMaster et al, 2018). The low levels of distress may have been due to low overall exposure to violence, as refugees who had been kidnapped were more likely to be diagnosed with PTSD (Wright et al, 2017), and specific traumas were associated with more distress (Arnetz et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Participants were interviewed by a research assistant using a semi-structured survey in Arabic. The survey contained previously used and largely validated and published items or scales [8,11]. Demographics included age, gender, and country displaced from (Iraq or Syria).…”
Section: Survey Questionsmentioning
confidence: 99%
“…War-associated trauma is a major risk factor for the development of mental health disorders, including post-traumatic stress disorder (PTSD), depression, and anxiety [3][4][5][6][7]. Prospective studies of newly arrived refugees suggest that both pre-and post-displacement stressors contribute to adverse health trajectories [8][9][10][11]. Little is known, however, about the possible implications of environmental exposures for mental health and the role of biomarkers reflective of disease mechanisms in refugee populations.…”
Section: Introductionmentioning
confidence: 99%